Analisis Kinerja Antena Pasif sebagai Penguat Sinyal Seluler - Zaini Zaini (Jurnal Sinergi Jurusan Teknik Mesin, 2023)
Cellular signal reception in a place must always be good, so that the services perceived by the recipient such as calls, text, and data/internet are in a stable condition. If the condition of the received signal is weak (unstable) it is necessary to improve the signal power both on the transmitter and receiver side, however, the weak signal reception occurs in a certain area with narrow coverage such as a room, house, and the like, it is necessary to strengthen the signal only at that location. In this study, I would like to propose that signal amplification is carried out by placing a passive antenna which functions to capture signals directly from the BTS, then transmits the signal to the receiver's position via cable, and the receiver brings closer or attaches the cellphone to the end of the cable. The results of the simulation and measurement research show that the parameter value of VSWR is 1.5, impedance (Z) is 75-j30.8Î©, antenna gain is 3.27 dB, bandwidth is 23 mHz. while the results of the application of the antenna in the head room of the Ujung Pandang State Polytechnic library, the antenna gain reaches 5-6 dB with a transmission cable length of 10-30 meters, cable impedance of 50 Î© and 75 Î©.